Efektifitas Pengembangan Lembar Kerja Peserta Didik (LKPD) Fisika SMA Berbasis Model Pembelajaran Generatif - Saputri, Ririn Hustia; Deswita, Pipi; Fauzi, Ahmad; Wulan, Ratna (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The purpose of this study was to see the effectiveness of the development of high school physics student worksheets (LKPD) based on generative learning models. This development research uses a 4-D model. To see the effectiveness of the product, a develop step is carried out. The research sample was students of class X SMAN 1 Bayang Utara, Pesisir Selatan Regency. The results showed that LKPD was very effective in increasing the competence of attitudes, skills, and knowledge of students, with an average rating as follows: 76.47% effective category; Skills 80.48% very effective category; Knowledge of 81.58% category is very effective. This shows that the High School Physics Student Worksheet (LKPD) based on the Generative Learning Model can be used to improve the competence of Attitudes, Skills, and Knowledge of class X SMA students on dynamic electricity material.